Maternal Height, Maternal Education Level, and Occurrence of Stunting in Families with Overweight or Obese Mothers - Arisanti, Yohanete Novita; Purwanti, Rachma; Syauqy, Ahmad; Margawati, Ani (poltekkes kemenkes mataram, 2025)
Stunting can affect brain development, physical growth, and metabolism, while obesity can increase the risk of hypertension, coronary heart disease, and type 2 diabetes. Maternal and family characteristics may influence obesity in mothers paired with stunting in children in the same household. This study examines the relationship between maternal and family characteristics and the occurrence of stunting in families with overweight or obese mothers in Semarang. This study used an observational, cross-sectional design. The sample was selected using purposive sampling, with 25 subjects per group, resulting in a total of 50 subjects across the two groups. Data on maternal and family characteristics were obtained through interviews using a validated questionnaire. Anthropometric measurements were conducted to obtain data on the weight, height, and nutritional status of mothers and children. Bivariate analysis used the Chi-square test to examine the odds ratio, while multivariate analysis employed multiple logistic regression. Bivariate analysis showed that the adequacy of energy and carbohydrate intake in toddlers and the maternal education level were significantly associated with stunting occurrence among households with an overweight/obese mother (SCOWT/SCOM). Multivariate analysis showed that the maternal height and education level were significantly associated with SCOWT/SCOM. Mothers with short stature had a 4.613 times higher risk, and mothers with primary to secondary education had an 8.205 times higher risk of SCOWT/SCOM. Maternal height and educational level are key factors in cases of stunted growth with SCOWT/SCOM.